RELIGIOUS MODERATION, EXPERT, SOCIAL MEDIA CONTENT NEWBIE?: RELIGIOUS EXTENSION OFFICERS IN SOCIAL MEDIA - Epafras, Leonard Chrysostomos; Kaunang, Hendrikus Paulus; Pratisti, Siti Aliyuna (al-Balagh : Jurnal Dakwah dan Komunikasi, 2024)
About sixty-seven thousand religious extension officers (Penyuluh Agama), representing six religions in the state service, are on the frontline of the massive campaign of religious moderation organized by the Ministry of Religious Affairs. They are the sole body with religious competence dealing with the increasing religious conservatism, radicalism, and extremism. The study observed Penyuluh's digital performance and agency in social media. It describes the complexity of their position within the challenge of religious extremism, the execution of a religious moderation campaign, and social media engagement. Data collection utilizes mixed methods, while the analysis employs netnographic and descriptive-inductive methods. The findings demonstrate the digital divide context, the tendency of Penyuluh to reproduce the structure, hence limiting their agency, limited digital mastery and digital literacy of many of Penyuluh, fragmented institutional information system, and the vulnerability of instant messenger engagement that is prone to epistemic bubble and echo chamber effects.